2009
DOI: 10.3758/app.71.2.281
|View full text |Cite
|
Sign up to set email alerts
|

A multistream model of visual word recognition

Abstract: Since the beginning of experimental psychology, researchers have been interested in how humans recognize words during reading. For example, Cattell (1886) hypothesized that words were processed analytically, as component letters, whereas Pillsbury (1897) hypothesized that words were processed holistically, as whole units. Investigators have inferred from the results of many studies that both types of processing are involved (e.g., Rayner & Pollatsek, 1989). However, few contemporary models of word recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 73 publications
7
36
0
Order By: Relevance
“…This resonates with the view that lower spatial frequencies reach cortical areas before higher spatial frequencies (e.g., Allen et al, 2009;Jordan et al, 2012Jordan et al, , 2014Patching & Jordan 2005a,b), and so, compared to slow readers, fast readers may be especially able to use lower spatial frequencies to help gain lexical access more rapidly. Indeed, this ability for fast readers could provide an effective bottom-up basis for influences of predictability that many argue are also part of fast reading (e.g., Hawelka et al, 2015;Hersch & Andrews, 2012;Long et al, 1994;Murray & Burke, 2003).…”
Section: Discussionsupporting
confidence: 67%
“…This resonates with the view that lower spatial frequencies reach cortical areas before higher spatial frequencies (e.g., Allen et al, 2009;Jordan et al, 2012Jordan et al, , 2014Patching & Jordan 2005a,b), and so, compared to slow readers, fast readers may be especially able to use lower spatial frequencies to help gain lexical access more rapidly. Indeed, this ability for fast readers could provide an effective bottom-up basis for influences of predictability that many argue are also part of fast reading (e.g., Hawelka et al, 2015;Hersch & Andrews, 2012;Long et al, 1994;Murray & Burke, 2003).…”
Section: Discussionsupporting
confidence: 67%
“…Kana words can be processed automatically on the basis of their word-level orthographic representation (Nakagawa and Sukigara, 2000). Therefore, if we apply the model described by Allen et al (2009) to our results, Kanji may be dominantly processed by the letter (or character)-level processing associated with the P-pathway, while word-level processing in the M-pathway may contribute more to Kana processing.…”
Section: Contribution Of Differential Sf Information To Kanji and Kanmentioning
confidence: 89%
“…HSF and LSF information are processed distinctly in the P-and M-pathways, respectively (Tobimatsu and Celesia, 2006). Allen et al (2009) suggested a possible link between reading and the parallel visual pathways. When reading, letter-level processing is distributed to the P-pathway, which responds to HSF information, while word-level processing occurs in the M-pathway, which is sensitive to LSF information.…”
Section: Contribution Of Differential Sf Information To Kanji and Kanmentioning
confidence: 99%
“…There is a growing body of research that indicates an important role in word recognition for different bands of spatial frequency information, from coarse-scale (low-frequency) information that describes the overall extent of a word to more fine-scale (high-frequency) information necessary to specify individual letters and features (Allen & Madden, 1990;Allen, Smith, Lien, Kaut, & Canfield, 2009;Boden & Giaschi, 2000;Dakin & Morgan, 1999;Jordan, 1990Jordan, , 1995Jordan & Bevan, 1996;Jordan & de Bruijn, 1993;Leat & Munger, 1994;Legge et al, 1985;Patching & Jordan, 2005a, 2005b.The disruption to normal spatial frequency content caused by increased letter spacing may mean that coarse-scale information corresponding to the overall extent of words is particularly distorted, making words in these conditions afford poor quality information about word extent and location, which may also interfere with saccadic programming. Further research is needed to determine the nature of the spatial frequency information that is afforded by words and the role that it plays in facilitating eye guidance.…”
Section: Discussionmentioning
confidence: 99%